The Influence of Brand Image and CRM on Customer Loyalty in the Fashion Industry in Lamongan (Case Study at World Hijab Outlet) - Linda Oktaviona; Indira Shofia Maulida; Ike Susanti; Lilik Uzlifatul Jannah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesian people have extensive knowledge about the fashion industry, and developments related to fashion in Indonesia are experiencing a very worrying acceleration. So that a company's life cycle can continue to operate, grow and achieve its goals, the fashion industry in Indonesia is increasingly tightening market competition. CRM and customer perception of brand image are important factors in building consumer loyalty. The purpose of this writing is to determine the impact of customer loyalty and (CRM) on brand image in the fashion sector in Lamongan. This writing category uses quantitative methodology, collecting data from a sample of 90 respondents by distributing questionnaires through survey techniques using random sampling. The analysis was carried out using SPSS version 26. The results of this paper show that the Brand Image (X1) and Customer Relationship Management (CRM) (X2) variables have a positive and significant effect on customer loyalty (Y).